Efeitos de dietas com e sem glúten sobre os dados antropométricos e dietéticos de mulheres eutróficas saudáveis - Hirla Karen Fialho Henriques (2018)
Introduction: Gluten is present in cereals, including wheat, rye, oats and barley. The gluten-free diet is based on the treatment of celiac disease. However, despite the scarcity of scientific studies evidencing its exclusion in the diet, there is a high increase in the adhesion of gluten-free diets as an alternative for weight loss. The objective of this work was to observe the effects of the exclusion of food sources of wheat gluten in the diet as well as the effect of this on body composition and dietary routine of non-celiac eutrophic women. METHODS: This is a single-blind, controlled trial whose sample was determined for convenience. The volunteers were divided into two treatments: gluten and gluten free for three weeks, after which they migrated from treatment and maintained the diet free of treatment. They were oriented to consume test food containing wheat gluten (15g / day) or without gluten. Anthropometric assessments, body composition, energy expenditure, dietary assessment and presence of gastrointestinal symptoms were performed. Results: The study totaled 23 volunteers, 11 of whom started the intervention with gluten and 12 without gluten. They did not present relevant gastrointestinal symptoms in any of the treatments. The results show that, during the 3-week gluten-free diet, reductions in body weight and BMI were not statistically significant. However, there is an increase in fat mass and percentage of fat in this treatment, in addition to a reduction of lean mass (kg). On the other hand, after 3 weeks of gluten supplementation, there was a discrete but significant weight loss, association with calorie reduction and protein increase. Conclusion: Our results suggest that the adoption of exempt diets had no significant effect on body weight but reduced lean mass and increased body fat mass. And weight loss in gluten treatment was related to reduced caloric intake, increased protein intake and reduced carbohydrate, without changes in dietary lipids.